Real estate valuation, current account, and credit growth patterns before and after the 2008 - 2009 crisis - Joshua Aizenman; Yothin Jinjarak (Asian Development Bank Institute (ADBI), 2013)
This paper explores the stability of the key conditioning variables accounting for real estate valuation before and after the crisis of 2008 - 2009, in a panel of 36 countries, for the period of 2005:I - 2012:IV, recognizing the incidence of global financial crisis. Our paper validates the robustness of the association between the real estate valuation of lagged current account patterns, both before and after the crisis. The results are supportive of both current account and credit growth channels, with the animal-spirits and momentum channels playing the most important role in the boom and bust of real estate valuation.
Keywords: F15; F21; F32; R21; R31; 330; current account; real estate; credit supply; global crisis; housing boom; Finanzkrise; Immobilienpreis; Leistungsbilanz; Kreditgeschäft; Welt